A Pardigm for Economic Growth in the 21st Century (Global Journal of Human-Social Science, 2017)
This study presents a paradigm for determining economic equilibrium in economic systems The economic disequilibria curve is introduced and shows the robust correlation between productivity and exchange rates and plots the optimal rate of economic growth and interest rates along the economic disequilibria curve This study examines the evidence for a productivity based model of the dollar euro real exchange rate Cointegrating relationships between the real exchange rate and productivity real price of oil and government spending are estimated using the Johansen and Stock-Watson procedures The findings show that for each percentage point in the US-Euro productivity differential there is a three point change in the real dollar euro valuation These findings are robust to the estimation methodology the variables included in the regression and the sample period Watson procedures The findings show that for each percentage point in the US-Euro productivity differential there is a three point change in the real dollar euro valuation These findings are robust to the estimation methodology the variables included in the regression and the sample period
Keywords: exchange rates; labor productivity and economic growth and equilibrium